The loyalty of Pagar Alam City Tourists in terms of Segmenting, Targeting, and Positioning - Elvera Elvera (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This research is aimed to analyze the effect of Segmenting, Targeting, dan Positioning on the loyalty of Pagar Alam City tourists. The population of this study is tourists who came or visit Pagar Alam City. The sampling technique used purposive sampling that the population was taken based on certain criteria namely the tourists who lived outside Pagar Alam City and have traveled to Pagar Alam City, with 400 respondents as the sample. The statistical analysis technique used in this study is multiple regression. The result of this research showed that partially segmenting, targeting, and positioning had a positive effect and significance on tourist loyalty. Next, simultaneously segmenting, targeting, and positioning also had a positive and significant effect on tourist loyalty. It means that the better application of segmenting, targeting, and positioning, the higher tourist loyalty in Pagar Alam City. Thus, it is recommended for tourism managers in this case the Tourism Office of Pagar Alam City to improve targeting and better positioning so that tourists have positive expectations for tourist destinations in Pagar Alam City. In the end, positive tourist expectations can increase loyalty to tourist destinations in Pagar Alam City.